Implementasi Firebase Cloud Messaging (FCM) Pada Aplikasi Agenda Rapat - Firaninda Cahya Prista; Sri Wulandari (JSAI (Journal Scientific and Applied Informatics), 2024)
One type of activity of the HIMATIKA UTY organization is holding meetings. This activity is carried out regularly during the management period. However, the management of meeting activities is still done manually so it is not efficient. The purpose of this research is to build the HIMATIKA UTY Meeting Agenda application which is used to optimize the implementation of meeting activities. The system built in this study will implement Firebase Cloud Computing (FCM) which is used by the secretary and management. This application serves to facilitate the secretary in managing meeting activities, managing attendance and submitting permits, and providing notifications to the management if there is a meeting schedule, minutes, or meeting information. Based on the SUS score of 89.08, this system falls into the “Highly Satisfactory” category, indicating that users overall have a very good experience using the system. This figure shows that the system has met the standards of ease of use and good interaction quality.